Dinuclear Cobalt Complexes for Homogeneous Water Oxidation: Tuning Rate and Overpotential through the Non‐Innocent Ligand. Issue 21 (27th September 2022) - Hsu, Wan‐Chi; Zeng, Wan‐Qin; Lu, I‐Chung; Yang, Tzuhsiung; Wang, Yu‐Heng
Abstract: In this study, dinuclear cobalt complexes (1 and 2 ) featuring bis(benzimidazole)pyrazolide‐type ligands (H2 L and Me2 L ) were prepared and evaluated as molecular electrocatalysts for water oxidation. Notably, 1 bearing a non‐innocent ligand (H2 L ) displayed faster catalytic turnover than 2 under alkaline conditions, and the base dependence of water oxidation and kinetic isotope effect analysis indicated that the reaction mediated by 1 proceeded by a different mechanism relative to 2 . Spectroelectrochemical, cold‐spray ionization mass spectrometric and computational studies found that double deprotonation of 1 under alkaline conditions cathodically shifted the catalysis‐initiating potential and further altered the turnover‐limiting step from nucleophilic water attack on (H2 L )Co III 2 (superoxo) to deprotonation of (L )Co III 2 (OH)2 . The rate–overpotential analysis and catalytic Tafel plots showed that 1 exhibited a significantly higher rate than previously reported Ru‐based dinuclear electrocatalysts at similar overpotentials. These observations suggest that using non‐innocent ligands is a valuable strategy for designing effective metal‐based molecular water oxidation catalysts. Abstract : Not so innocent : The potential of engineering molecular (electro)catalysts using non‐innocent ligands for water oxidation and other energy‐related reactions to improve their catalytic performance in terms of kinetics (turnover frequency) and thermodynamics (overpotential) is evaluated.